Impact points and their effect on trajectory in soccer - Kimachi, K.; Hong, S.; Shimonagata, S.; Asai, T. (Proceedings, 2018)
The kick skill and its analysis are important in Soccer. To detect impact point by using virtual impact model is aim of this study. The virtual impact model was made as a surface composed of virtual markers. As the result, mean coordinate values of impact point were below; straight (Lateral: -24.0 ± 5.6 mm, Horizontal: 152.7 ± 8.4 mm, Vertical: 52.3 ± 4.0 mm), curve (Lateral: -35.6 ± 4.8 mm, Horizontal: 151.6 ± 13.7 mm, Vertical: 47.5 ± 5.2 mm), knuckle (Lateral: -33.3 ± 9.0 mm, Horizontal: 140.8 ± 10.7 mm, Vertical: 52.1 ± 2.7 mm). According to comparison of coordinate value of each trial, mean point of straight was near the center line of foot on instep, mean point of curve was located on inside of foot, mean point of knuckle was near the foot joint. We revealed difference of impact point and showed trajectory of impact point.